2011
DOI: 10.1103/physrevb.84.161301
|View full text |Cite
|
Sign up to set email alerts
|

Electrically controlled pumping of spin currents in topological insulators

Abstract: Pure spin currents are shown to be generated by an electrically controlled quantum pump applied at the edges of a topological insulator. The electric rather than the more conventional magnetic control offers several advantages and avoids, in particular, the necessity of delicate control of magnetization dynamics over tiny regions. The pump is implemented by pinching the sample at two quantum point contacts and phase modulating two external gate voltages between them. The spin current is generated for the full … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 49 publications
5
66
0
Order By: Relevance
“…27 It can be used for creating on-demand pure spin-current. [28][29][30][31][32] The Article is structured in the following way: we start by presenting the SpPS set-up (Sec. II), then we show the results for the emitted current and noise (Secs.…”
Section: Introductionmentioning
confidence: 99%
“…27 It can be used for creating on-demand pure spin-current. [28][29][30][31][32] The Article is structured in the following way: we start by presenting the SpPS set-up (Sec. II), then we show the results for the emitted current and noise (Secs.…”
Section: Introductionmentioning
confidence: 99%
“…In the central region of the setup, the two edge states are coupled by electron tunneling. The tunneling Hamiltonian that preserves time-reversal symmetry consists of two terms [29][30][31][32][33][34][35] , H tun =Ĥ p tun +Ĥ f tun , wherê…”
Section: Modelmentioning
confidence: 99%
“…[24][25][26][27] For the helical states, a constriction in the QSH bar causes a local wavefunction overlap 28,29 that is known to yield two types of tunneling processes. [29][30][31][32][33][34][35][36][37][38][39] The first type is the customary spin-preserving (p) process, where an electron tunnels across the junction maintaining its spin orientation, and thereby reversing its group velocity. The second type is less conventional and is a spin-flipping (f ) process, where a tunneling electron reverses its spin orientation maintaining its group velocity: it mainly originates from the interplay between bulk-inversion asymmetry and wavefunction overlap, even in absence of magnetic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that in the weak coupling limit, topological spin pumps are characterized by the appearance of symmetryprotected gapless end states during the pumping cycle, similarly to the Z 2 pump. Several different methods have been put forward to realize the Z 2 pump experimentally, including a Luttinger liquid [34], a double-corner junction in a topological insulator [35], and quantum wires proximity coupled to a superconductor [36].…”
Section: Introductionmentioning
confidence: 99%